Durability and expansion of neutralizing antibody breadth following Ad26.COV2.S vaccination of mice - Shant H. Mahrokhian; Lisa H. Tostanoski; Catherine Jacob-Dolan; Roland C. Zahn; Frank Wegmann; Katherine McMahan; Jingyou Yu; Makda S. Gebre; Esther A. Bondzie; Huahua Wan; Olivia Powers; Tianyi Ye; et al. (npj Vaccines, 2022)
Abstract Emerging SARS-CoV-2 variants with the potential to escape binding and neutralizing antibody responses pose a threat to vaccine efficacy. We recently reported expansion of broadly neutralizing activity of vaccine-elicited antibodies in humans 8 months following a single immunization with Ad26.COV2.S. Here, we assessed the 15-month durability of antibody responses and their neutralizing capacity to B.1.617.2 (delta) and B.1.351 (beta) variants following a single immunization of Ad26.COV2.S in mice. We report the persistence of binding and neutralizing antibody titers following immunization with a concomitant increase in neutralizing antibody breadth to delta and beta variants over time. Evaluation of bone marrow and spleen at 15 months postimmunization revealed that Ad26.COV2.S-immunized mice tissues contained spike-specific antibody-secreting cells. We conclude that immunization with Ad26.COV2.S elicits a robust immune response against SARS-CoV-2 spike, which expands over time to neutralize delta and beta variants more robustly, and seeds bone marrow and spleen with long-lived spike-specific antibody-secreting cells. These data extend previous findings in humans and support the use of a mouse model as a potential tool to further explore the dynamics of the humoral immune response following vaccination with Ad26.COV2.S.